Improving E-Sport Player Loyalty: An Overview of the Game Industry in JABOTABEK, Indonesia - Widjaja, William; Samudra , Andika; Chairuddin; Rachman, Adryan; Alvita, Meilisa (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research Aim: This study investigates the impact of experiential values ​​and promotional activities on player satisfaction, which affects player loyalty in the e-sports industry in the Jabodetabek area. Approach: This study uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach to test the proposed hypotheses and achieve the research objectives. Questionnaires were distributed to 100 respondents who identified as e-sports players in the Jabodetabek area. Research Findings: This study found that experiential values ​​have a positive and significant effect on player satisfaction in the e-sports industry in the Jabodetabek area. However, promotional activities do not significantly affect e-sports player satisfaction. This means that esports companies' promotional efforts may not significantly impact player satisfaction. Theoretical Contribution: This finding suggests that the theory of satisfaction on loyalty also applies to the Jabodetabek esports industry. Practical Implications: This study has significant practical implications for e-sports companies looking to enhance the value of the player experience by increasing the complexity of their games' features. Research Limitations: This study is limited to the Jabodetabek area and may not reflect the same conditions in other areas.